Study on Biodiversity Conservation Practice in Madhupur Sal Forest, Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted in Madhupur Sal Forest, which is very well known for its characteristics as deciduous forest, to describe the diversity of plant species and animal species and to examine the diversity status in Madhupur Sal Forest. A stratified random quadrate method was employed in the study. A total of 40 plant species were recorded of which 21 were tree species, 9 were herbs, 5 were shrubs and rests 5 were climbers. Total 17 animal species were recorded of which 9 were birds, 3 were amphibians, 2 were reptiles and 3 were mammals. With regards to the quantitative attributes of total flora and fauna species, the highest number was found in trees (mean, 14.20) and the lowest number was found in mammals (mean, 0.80). The result showed very high significant variation among them. It was evident from the study that the people around the forest collect forest flora (75.45%) and fauna (8.18%) illegally is the major cause of biodiversity loss. The people are not aware of the importance of forest in various aspects like social, economical, ecological and environmental aspects. Forest authorities are trying to involve the people in and around the forest in community forestry through motivation and training.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22064 J. Environ. Sci. & Natural Resources, 6(1): 187-193 2013